A broadband stable gain antenna using nonuniform hexagonal-Slot metasurface. Issue 7 (3rd October 2022) - Fan, Yue; Li, Zhi; Zheng, Zijun; Han, Guorui; Han, Liping; Zhang, Wenmei
ABSTRACT: This paper demonstrates a broadband metasurface antenna with stable gain. A 4 × 4 square patches metasurface loaded with nonuniform hexagonal slots is proposed. To achieve stable radiation performance in broadband range, two characteristic modes with the same current direction are selected as operating modes of the metasurface. A slot antenna is employed to excite the metasurface. By combining the resonant modes of metasurface and slot antenna, the broadband is obtained. The measured results show that, the −10 dB impedance bandwidth of the proposed antenna is 4.36–8.21 GHz (61.2%), the 2 dB gain bandwidth is 4.36–7.2 GHz (49.1%), and the peak gain value reaches 10.6 dBi.